The Influence of Price and Ease of Access to Decisions Purchase of Shallot Commodities by Traders in the Market New Jati Asih, Bekasi - Alexander Wahyu Adi , Alexander Wahyu Adi; Bachtar Bakrie, Bachtar Bakrie; Eko Sembodo, Eko Sembodo (Journal of Entrepreneur and Business, 2023)
Shallots are one of the vegetable commodities that are consumed by the community regularly as a daily necessity. Shallot commodity prices in the market tend to fluctuate, because the production process is influenced by the season. This research was conducted with the aim of studying the effect of price and ease of access on the purchasing decisions of shallots by traders at Pasar Baru Jati Asih Bekasi. This research is a survey with a quantitative approach, using a sample of 200 traders which is a purposive sample, taken as a quota from the population, namely all vegetable traders in Pasar Baru Jati Asih Bekasi. Data was collected by questionnaire, using data analysisStructural Equation Modelling(SEM). The results showed that price had a positive and significant effect on ease of access, ease of access had a positive and significant effect on purchasing decisions for shallots, while price did not have a significant effect on purchasing decisions even though it had a positive effect. Keywords: price, access, buying decision